Abdominal pain as initial presentation of lung cancer. (16th May 2014) - Eisa, Naseem; Alhafez, Bishr; Alraiyes, Abdul Hamid; Alraies, M Chadi
Abstract : Isolated spleen metastasis (ISM) in general is very rare with a reported incidence of 2.3–7.1% for all solid cancers. Lung cancers rarely metastasise to the spleen. It is very atypical for ISM to be the initial presentation of lung cancer as well. In our case, a 55-year-old woman presented with a 3-week history of left-sided abdominal fullness and dull pain. Workup was remarkable for splenic mass that turns out to be adenocarcinoma with unknown primary tumour. Biopsy of the mass with immunohistochemistry and whole body position emission tomography scan was able to identify lung cancer as the primary tumour. The patient underwent splenectomy, wedge resection of the lung mass along with short-course of chemotherapy. She never had any recurrences since then.